Social Movement of Borneo Orangutan Survival Foundation (Bos) Foundation Based on Communities In Orangutan Safety In Central Kalimantan - Arum Silviana; M. Masduki; Tri Sulistyangingsih (Universitas Muhammadiyah Malang, 2018)
The Borneo Orangutan Survival Foundation (BOS) Foundation is an Indonesian non-profit organization dedicated to the conservation of the Bornean Orangutan and its habitat. The BOS Foundation is the largest reintroduction program in the world. This study aims firstly to describe the process of community-based social movements conducted by the Borneo Orangutan Survival Foundation (BOS) Foundation and secondly to describe the type and motive of social movement actors that give awareness of the importance of orangutan conservation. This research type is descriptive research. This study aims to describe the phenomenon in addressing Central Kalimantan Orangutan. The approach used is case study. The results of this study indicate that the emergence of BOS movement is caused by an endangered orangutan population. The destruction of forests has resulted in this endangered orangutan population, the loss of biodiversity, as well as rising greenhouse gas emissions that could trigger global warming. In addition to the impact of forest fires in 1997, the ex-PLG Million Ha area also caused a decrease in the Orangutan population. Therefore, BOS is present to make efforts to save the Orangutan